2020
DOI: 10.1063/1.5128693
|View full text |Cite
|
Sign up to set email alerts
|

Ion pair free energy surface as a probe of ionic liquid structure

Abstract: Numerous combinations of cations and anions are possible for the production of ionic liquids with fine-tuned properties once the correlation with the molecular structure is known. In this sense, computer simulations are useful tools to explain and even predict the properties of ionic liquids. However, quantum mechanical methods are usually restricted to either small clusters or short time scales so that parameterized force fields are required to study the bulk liquids. In this work, a method is proposed to ena… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…It is known that the introduction of polarizability weakens the long-range structure in relation to the short-range structure of ILs, and that produces significant effects over the dynamics of the IL. 52,54,55 Here, our model reproduces the rheology as well as the polarizable model (Fig. 4), however, an overall reduction of electrostatic interactions instead of the introduction of explicit polarizability may lead to an overstructation in long-range and understructuration at the first coordination shell.…”
supporting
confidence: 53%
“…It is known that the introduction of polarizability weakens the long-range structure in relation to the short-range structure of ILs, and that produces significant effects over the dynamics of the IL. 52,54,55 Here, our model reproduces the rheology as well as the polarizable model (Fig. 4), however, an overall reduction of electrostatic interactions instead of the introduction of explicit polarizability may lead to an overstructation in long-range and understructuration at the first coordination shell.…”
supporting
confidence: 53%
“…Hamiltonian 23 as implemented in the MOPAC software. 24 More recently, it was shown that free energy surfaces of first coordination shell of ion pairs of ionic liquids obtained at DFT level produces results in excellent agreement with the ones obtained from liquid phase MD simulations, 25,26 demonstrating that even in some complex cases, Themis is able to probe the structure of condensed phases. This enables the comparison of forcefields with higher theory methods such as DFT, which are too costly to be applied even for small clusters.…”
Section: Resultsmentioning
confidence: 73%
“…4 Ionic liquids (ILs), comprised of anions and cations, show many advantages such as low vapor pressure and wide electrochemical window. 5,6,[18][19][20] The HB networks in ILs play a very important role in their physicochemical properties. 5,6,[21][22][23] Gamrad et al.…”
Section: Introductionmentioning
confidence: 99%